1989
DOI: 10.1177/37.11.2553800
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of 1,25-dihydroxyvitamin D3 receptors and estrogen receptors by monoclonal antibodies: comparison of four immunoperoxidase methods.

Abstract: We developed an immunohistochemical method for visualization of vitamin D (VDR) and estrogen receptors (ER) in cryostat sections, using monoclonal antibodies (MAb) to the vitamin D receptor and estrogen receptor, respectively. This method is based on an avidin-biotin labeling technique (LAB). To establish a reliable and sensitive method which can be used easily as a routine diagnostic procedure, we systematically compared four different immunoenzymatic methods with respect to their efficiency in detecting vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 0 publications
4
22
0
1
Order By: Relevance
“…To modulate the transcription of target genes in response to its cognate ligand 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ), VDR must be localized in nucleus and then bind to an enhancer designated as the vitamin D-responsive element (VDRE), forming a heterodimer with retinoid X receptor (1)(2)(3)(4)(5)(6). In contrast to the case for the glucocorticoid receptor (GR), which translocates from the cytoplasm to the nucleus when exposed to its ligand, VDR does not bind to heat shock protein 90, and both immunocytochemical and biochemical fractionation studies suggested the nuclear localization of VDR even in the absence of 1,25(OH) 2 D 3 (7)(8)(9)(10).…”
Section: The Vitamin D Receptor (Vdr)mentioning
confidence: 99%
“…To modulate the transcription of target genes in response to its cognate ligand 1,25-dihydroxyvitamin D 3 (1,25(OH) 2 D 3 ), VDR must be localized in nucleus and then bind to an enhancer designated as the vitamin D-responsive element (VDRE), forming a heterodimer with retinoid X receptor (1)(2)(3)(4)(5)(6). In contrast to the case for the glucocorticoid receptor (GR), which translocates from the cytoplasm to the nucleus when exposed to its ligand, VDR does not bind to heat shock protein 90, and both immunocytochemical and biochemical fractionation studies suggested the nuclear localization of VDR even in the absence of 1,25(OH) 2 D 3 (7)(8)(9)(10).…”
Section: The Vitamin D Receptor (Vdr)mentioning
confidence: 99%
“…Negative controls were performed using tris-buffered saline (TBS) instead of primary antibody and positive controls employing duodenal cross-sections of pigs (cross-reactivity proven and giving identical results; Milde et al, 1989;Schröder et al, 2001). In every tissue specimen, .…”
mentioning
confidence: 99%
“…Following the avidin-biotin block (20 min each, Vector Laboratories, Burlingame, Calif., USA), a serum-free protein block (10 min, DakoCytomation, Zug, Switzerland) was kept in a humidified chamber. Sections were rinsed in TBS and incubated for 80 min with a biotinylated rat monoclonal antibody (9A7 ␄ , NeoMarkers) directed against chicken VDR protein (aa 89-105) demonstrating cross-reactivities with pig and sheep VDR [Milde et al, 1989;Schröder et al, 2001]. This step was followed by rinsing in TBS (5 min), incubation with StreptABComplex/HRP (30 min, DakoCytomation), rinsing in TBS (5 min) and incubation with diaminobenzidine tetrahydrochloride chromogen and H 2 O 2 (Dakocytomation) for 3 min and rinsing with TBS (5 min).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…There is growing direct evidence that the traditional nuclear VDR may also have a unique, non-transcriptional role in plasma membrane-initiated signalling [Fleet, 2004]. This would to some extent explain the detection of VDR in the cytoplasm of target cells [Feldman et al, 1979;Milde et al, 1989;Barsony et al, 1997;Zineb et al, 1998;PrĂŒfer et al, 2000;Horst et al, 2003] -a locus where the receptor protein is synthesized.…”
mentioning
confidence: 99%